Supergirl. The complete fifth season [videorecording (DVD)] - Benoist, Melissa; Brooks, Mehcad, 1980-; Jordan, Jeremy, 1984-; Leigh, Chyler, 1982- (Warner Home Video, 2020)
Season four showed that truth, justice and the American way are stronger than fear and hate, as Supergirl stopped Lex Luthor's anti-alien campaign with the power of the press, no cape required. As the world returns to normal, some things will never be the same now that Lena knows Kara's secret and the Monitor has arrived on Earth 38! New adventures are in store for Supergirl in season five.